Corruption, governance and sustainable development - Lameira, V. (2016)
This paper presents a methodology for evaluating the relationship between governance and several variables commonly related to the concept of sustainable development, using financial indicators for control. We explore the theoretical framework linking the level of governance of the countries with their performance. Our sample incorporates data from developed and emergent countries, collected from the World Bank and Transparency International, to assess the significance of governance impact among countries with distinct degrees of development. Multiple regression analysis and panel data modelling were used to explore statistical relations amongst variables. Results show a positive relation between levels of governance and economic development, aside from illustrating other significant issues.